Opportunities for improving abortion care: a key stakeholder analysis of best practices for addressing the needs of transgender, nonbinary, and gender expansive people seeking abortions - Aliza J. Barnett; Subasri Narasimhan; Sophie A. Hartwig; Anna Newton-Levinson (BMC, 2024)
Abstract Objectives Transgender, nonbinary, and gender expansive (TGE) persons experience pregnancies and have abortions, yet abortion care remains rooted in a gender binary, often centering the needs, experiences, and challenges of cisgender women. Despite guidance supporting gender-affirming sexual and reproductive healthcare (SRH), barriers for TGE people seeking abortions persist. We conducted an exploratory case study with key informants to understand their perception of TGE abortion seekers' needs with specific considerations for those in restrictive abortion settings. Methods Qualitative interviews focused on gender-affirming care and abortion provision were conducted with U.S.-based key informant clinicians (n = 4) who could provide powerful insights into gaps and experiences faced by TGE individuals. Participants were eligible if they currently or previously provided abortions and had experience practicing gender-affirming care. Interviews focused on informants' perceptions of TGE patients' needs when seeking abortions. Results Findings highlight the unique barriers TGE patients face when seeking abortions, including lack of provider knowledge, in-clinic stigmatization, and gender marginalization. It is notable that key informants who practiced in abortion-protective political environments have greater access to resources to implement gender-affirming care than those in restrictive contexts. Results are summarized in a clinical recommendations document which provides an accessible starting point for clinicians to begin building gender-inclusive abortion spaces. Conclusions It is necessary to further understand barriers facing TGE abortion seekers and integrate recommendations and emerging evidence into abortion practice. This study contributes to a growing knowledge base which emphasizes the need for inclusive abortion spaces and highlights key considerations for improving access and quality for TGE abortions seekers.